2000
DOI: 10.1021/jp9931511
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Governing Microparticle Morphology during Precipitation by a Compressed Antisolvent:  Atomization vs Nucleation and Growth

Abstract: This study provides insight into the mechanisms that govern morphology in microparticles processed using precipitation by a compressed antisolvent. We explore the time scale of surface tension evolution in jets of miscible fluids injected into critical and near-critical solvents to determine whether the jets atomize into droplets or simply evolve as gaseous plumes. Classical jet breakup length equations, modified with timedependent surface tension, accurately predict observed breakup lengths over a range of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 37 publications
5
78
0
2
Order By: Relevance
“…13,14 The TEM images revealed the encapsulation of paracetamol inside biodegradable polymer, as shown in Figure 6. For personal use only.…”
Section: Structure Of Nanoparticlesmentioning
confidence: 98%
“…13,14 The TEM images revealed the encapsulation of paracetamol inside biodegradable polymer, as shown in Figure 6. For personal use only.…”
Section: Structure Of Nanoparticlesmentioning
confidence: 98%
“…Lengsfeld et al were the first group that investigated fluid dynamics of the SAS process, studying the evolution and disappearance of the liquid surface tension of fluids injected in supercritical carbon dioxide. They concluded that a gas-like jet is formed after the jet break-up (Lengsfeld et al, 2000). In this way, Kerst et al determined the boundaries between the different modes and they noted a strong interdependence between mass transfer and fluid dynamics (Kerst et al, 2000).…”
Section: Parameters Influence On Hydrodynamicmentioning
confidence: 99%
“…Lengsfeld et al [86] developed a method for predicting dynamic surface tension and combined this method with linear jet breakup equations to accurately predict jet breakup lengths in immiscible to highly miscible systems. For highly miscible systems, they proposed that microparticle formation results from gas-phase nucleation and growth within the expanding plume, rather than by nucleation within discrete liquid droplets.…”
Section: Fluid Dynamicsmentioning
confidence: 99%